2010
DOI: 10.1212/wnl.0b013e3181eccf78
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment ASPECTS on DWI predicts 3-month outcome following rt-PA

Abstract: ASPECTS on DWI was independently predictive of functional and vital outcomes at 3 months, as well as sICH within 36 hours, following rt-PA therapy for stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 33 publications
2
79
0
1
Order By: Relevance
“…DWI and perfusion-weighted imaging have demonstrated prognostic value in acute anterior ischemic stroke. 11,12 In previous studies on vertebrobasilar ischemic stroke, the acute global DWI lesion volume did not correlate with the baseline NIHSS score. 13,14 More recently, investigators have studied the functional outcome and extent of lesions in patients with a posterior circulation infarction by diffusion-weighted MR imaging.…”
mentioning
confidence: 86%
“…DWI and perfusion-weighted imaging have demonstrated prognostic value in acute anterior ischemic stroke. 11,12 In previous studies on vertebrobasilar ischemic stroke, the acute global DWI lesion volume did not correlate with the baseline NIHSS score. 13,14 More recently, investigators have studied the functional outcome and extent of lesions in patients with a posterior circulation infarction by diffusion-weighted MR imaging.…”
mentioning
confidence: 86%
“…14 In addition, a DWI-ASPECTS of Ͼ7 has been shown to be a good prognostic factor for patients. 14,19 This was also observed in our setting, though it did not reach statistical significance, possibly due to a suboptimal sample size. Our findings also confirmed that the initial clinical severity on presentation is correlated to the clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As described, the ASPECTS was applied to the DWI sequence to evaluate the parenchymal extension of the ischemic lesion. 14 Once the decision to treat was made, IVT was immediately administered. In the first study period, alteplase alone (0.9 mg/Kg) was infused with systematic clinical examinations (NIHSS score) at 1 hour and 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is some division over the utility of ASPECTS in the pre-intervention stage in predicting 90 day outcome and mortality. A number of papers show that a higher ASPECTS of >7 is associated with improved outcomes in intra-arterial thrombolysis [15][16][17]33], with lower scores associated with poorer recanalisation and increased risk of haemorrhage. However, none directly compare younger with older patient age groups, although one study using IAT investigated ASPECTS specifically in the elderly (>80 years age group, [34]).…”
Section: Differences In Factors Predicting Outcome and Mortality Aftementioning
confidence: 99%
“…The different modes have been shown to yield similar scores, though MRI-ASPECTS tends to score lower; however, many patients have contraindications to MRI on an acute admission [13,14]. ASPECTS has been shown in many studies investigating both thrombolysis and endovascular intervention (intra-arterial thrombolysis) to be an independent predictor of outcome, often with a threshold of <8 at admission heralding poorer function at 3 months [15][16][17]. On the other hand, some studies do not agree on the significance of early ischaemic changes on CT as predictors of long term functional outcome [18].…”
Section: Introductionmentioning
confidence: 99%